Opportunities for wooden furniture and wood products in United Kingdom, Netherlands and North America (CEDP St. Michael, BarbadosBB, 1992)
For each country gives detailed description of each niche market. Discusses market and product trends, structure of sectors, distribution patterns, pricing, industry standards, legal requirements, labelling, market access, transport and pcakaging. Contains list of importers and buying groups.
DC